EXPOSING HYPOVIRULENT MYCOVIRUSES FOR FUTURE MANAGEMENT OF PHYTOPATHOGENIC FUNGI - Tijjni, Ibrahim; Lurwanu, Y. (FUDMA Journal of Sciences, 2023)
As a result of potential application of mycoviruses for the biological control of crop fungal diseases, attention of researchers now focused on identification and characterization of viruses infecting phytopathogenic fungi. Eventhough must of mycoviruses do not have specific effects on the plants or on their hosts fungi, those that reduce the virulence of their phytopathogenic fungal hosts are highly needed to develop an alternative approach to biological control of phytopathogenic fungi, other than fungicides. Mycoviruses that infect endophytic fungi and those that encode killer toxins are also of special interest. Most of the previous studies mainly reported the presence of viruses in the pathogenic fungi with little information about the hypovirulence and relationships with the host plant. Hence, knowledge and understanding hypovirulence of fungal viruses is still in its infancy. Greater understanding of the viruses of fungal endophytes may therefore be helpful for practicing sustainable agriculture, particularly considering their potential application for the biological control of crop fungal diseases. Here in, we explored reports on hypovirulence of mycoviruses for future biological control against fungal diseases.